Diplomatic transformation and developing a new type of international relations: A perspective to observe and understand new China’s diplomacy - Wang, Cungang (Napredak, 2021)
Since 1949, diplomacy of the People's Republic of China has successively undergone transformation for three times, namely diplomacy of establishing the PRC, diplomacy of enriching the country and major-country diplomacy. Developing a new type of international relations is an effective way to achieve diplomatic transformation of New China, but its connotations vary with different periods of history.During the two turnarounds from 1949 to 2012, New China’s diplomacy, which holds up the Principle of Independence and Five Principles of Peaceful Coexistence, took shape in the practice of developing a new type of international relations. The former principle have played an important role in safeguarding China's sovereignty and dignity, protecting national security and promoting the country’s development. The latter became basic norm of international relations and basic principle of international law due to its openness and inclusiveness.
Keywords: A new type of international relations; diplomatic transformation; China's diplomacy